Chemical characteristics of soil organic matter from integrated agricultural systems in southeastern Brazil. (21st June 2021) - Tadini, Amanda M.; Martin‐Neto, Ladislau; Goranov, Aleksandar I.; Milori, Débora M. B. P.; Bernardi, Alberto C. C.; Oliveira, Patricia P. A.; Pezzopane, José R. M.; Colnago, Luiz A.; Hatcher, Patrick G.
Abstract: Soil organic matter (SOM) plays an essential role in agronomic systems and is of great importance to environmental sustainability and carbon sequestration. This study evaluates the accumulation of carbon in soils from integrated agricultural systems (S) that include crop (C), livestock (L), and forest (F) components (in different combinations: CLFS, LFS and CLS) and an undisturbed native forest (NF) as a reference area. The study sites are part of the Embrapa Pecuária Sudeste research station located in the southeast of Brazil in a region of dystrophic Red‐Yellow Latosol soils. Stable carbon isotopic analysis (δ 13 C) and solid‐state 13 C nuclear magnetic resonance ( 13 C NMR) spectroscopy were used to evaluate the chemical characteristics of humic acid (HA) extracts of soils from different soil horizons. The findings were discussed in the context of laser‐induced fluorescence spectroscopy (LIFS) measurements on the whole soils and carbon content on both the whole soils and HA extracts. With increasing depth of the soil horizons, bulk SOM (in the whole soil) and a more recalcitrant humic fraction (the HA) became enriched in carbon, indicative of accumulation. Isotopic analysis revealed that SOM in the crop‐livestock‐forest system exhibited δ 13 C signatures corresponding to C4 plants (grass and corn). The native forest exhibited a uniform δ 13 C signature characteristic of C3 plants (native trees). Benzenepolycarboxylic acids (BPCA) quantification on limited samples revealed condensed aromatic structures in both crop‐livestock‐forest system and native forest. The absence of burning suggests that these compounds come from the humification of lignin. Based on structural characterization, carbon is sequestered as recalcitrant and long‐lived oxidized ligninaceous structures and condensed aromatic groups. The current research demonstrates the feasibility of novel agricultural approaches such as using crop‐livestock‐forest systems. Such pastureland management enhances higher agricultural productivity and sustainability, thus avoiding new deforestation of native areas. Highlights: Integrated agricultural systems enhance carbon enrichment in soil organic matter and humic acids. Carbon stabilized in oxidized ligninaceous and condensed molecules promotes long‐term carbon storage. Extended root systems are likely to play a critical role in carbon sequestration. Integrated agricultural systems can be effective alternatives for reducing greenhouse gases.